Social media users’ share intention and subjective well-being: An empirical study based on WeChat - Ma, Liang; Zhang, Xin; Yan Ding, Xiao (Online information review, 2018)
PurposeThe rise of social media has gained increasing attention in recent years; however, few studies have focused on social media users’ specific behavior and subjective well-being. To fill this research gap, the purpose of this paper is to develop an integrated model to investigate factors that affect social media user’s share intention and the relationship between user’s share intention and subjective well-being.Design/methodology/approachStructural equation model is used in this study. A field survey with 398 WeChat users is conducted to test the research model and hypotheses.FindingsThe empirical results show that: utilitarian value, hedonic value, user satisfaction and information source credibility are important factors affecting users’ share intention; users’ share intention positively affects user’s subjective well-being; moderating effects show that relative significance positively moderates the relationship between utilitarian value and users’ share intention; and users’ demographic characteristics differences actually exist in users’ share intention.Originality/valueFirst, the authors clear that factors affect social media users’ share intention from the perspective of customer-perceived value. The results deepen our understanding about the factors that affect WeChat users’ share intention. Second, the authors focus on the effect of users’ specific behavior on users’ subjective well-being and found that users’ share intention is one of the important aspects that affect user’s subjective well-being. More importantly, the authors tested users’ characteristic differences in social media users’ share intention, which have previously received limited attention.